PENGARUH INSENTIF DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KOMISI PEMILIHAN UMUM - JONI HERMAWAN; FIKRI (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2020)
This research aims to find out and analyze the effect of incentives and motivations of work partially and simultaneously on the performance of employees of madiun city election commission. This research uses a quantitative approach with survey methods. The research population is all employees of the Madiun City Electoral Commission (KPU) of 46 people. The sampling techniques in this study used census methods or with saturated sampling techniques. Research instruments are questionnaires that have tested their validity and reliability. Data analysis techniques use multiple linear regression analysis. The results of the study prove that: (1) Incentives partially affect the performance of employees of madiun city election commission. (2) Work motivation partially affects the performance of employees of madiun city election commission. (3) Incentives and motivation of work simultaneously affect the performance of employees of madiun city election commission.